Drug*placebo interaction effect may bias clinical trials interpretation: hybrid balanced placebo and randomized placebo-controlled design. Issue 1 (December 2016) - Hammami, Muhammad; Hammami, Safa; Al-Swayeh, Reem; Al-Gaai, Eman; Farah, Faduma; De Padua, Sophia
Abstract Background Conventional randomized placebo-controlled study design assumes the absence of drug*placebo interaction. We hypothesized the presence of such an interaction and that conventionally estimated drug effect might be biased. The objectives of the study were to determine the drug*placebo interaction effect (main) and compare conventionally estimated and interaction model-estimated drug effects (secondary). Methods We used a hybrid of balanced placebo and randomized placebo-controlled designs. Four hundred eighty healthy volunteers were randomized to three groups. The first received hydroxyzine (25 mg) described as hydroxyzine or placebo, the second received placebo described as hydroxyzine or placebo, and the third received hydroxyzine and placebo described as unknown; each in a randomized crossover design. Seven participants failed to crossover. Group assignment was concealed from participants and study coordinators. Coordinators were blinded to group and intervention assignment. Participants and coordinators were deceived as to study objectives. Main outcomes were mean area-under-the-curve of drowsiness (therapeutic outcome) and mouth-dryness (adverse outcome), self-reported on 100 mm visual analog scale over 7 h. Drug, placebo, placebo + interaction, and total effects were estimated using analysis of covariance by comparing received hydroxyzine/told placebo to received placebo/told placebo, received placebo/told hydroxyzine to received placebo/told placebo, received hydroxyzine/told hydroxyzine to received hydroxyzine/told placebo, and received hydroxyzine/told hydroxyzine to received placebo/told placebo, respectively. Drug effect was also conventionally estimated in the third group. Results Mean (SD) age was 31.4 (6.6) years, 65% were males. There was significant difference between placebo + interaction effect and placebo effect for both drowsiness and mouth-dryness with a mean difference (95% confidence interval) of 35.1 (5.6 to 64.6) and 23.8 (2.4 to 45.2) mm*hr, respectively. Total effect was larger than the sum of drug and placebo effects for drowsiness (139.7 (109.8 to 169.6) vs. 99.1 (68.2 to 130.0) mm*hr) and mouth-dryness (63.6 (41.1 to 86.1) vs. 34.7 (11.1 to 58.4) mm*hr). Conventionally estimated drug effect was larger than interaction model-estimated drug effect for drowsiness (69.2 (45.5 to 92.8) vs. (58.3 (31.6 to 85.0) mm*hr) and mouth-dryness (19.9 (5.3 to 34.5) vs. 9.5 (−9.2 to 28.1) mm*hr). Conclusions There is significant and important drug*placebo interaction effect that may bias conventionally estimated drug effect. Trial registration ClinicalTrial.gov identifier:NCT01501591 (registered December 25, 2011).